2014
DOI: 10.4028/www.scientific.net/kem.609-610.796
|View full text |Cite
|
Sign up to set email alerts
|

The Fabrication of Trans-Scale Micro-Fuze Safety Device

Abstract: Fuze Micro-Electro-Mechanical System (MEMS) has become a popular subject in recent years. Studies have been done for the application of MEMS-based fuze safety and arm devices. The existing researches mainly focused on reducing the cost and volume of the fuze safety device. The reduction in volume allows more payloads and, thus, makes small-caliber rounds more effective and the weapon system more affordable. At present, MEMS-based fuze safety devices are fabricated mainly by using deep reactive ion etching (DRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For the fabrication of MEMS setback arming devices, nonsilicon-based micromachining technology (generally a lithography electroforming micro molding (LIGA) process or an ultraviolet-LIGA (UV-LIGA) process) and silicon-based micromachining technology (generally a deep reactive-ion etching (DRIE) process or a silicon-on-insulator (SOI) process) are commonly used. The cost of these processes is high, and no cheap mass production method has been found [24,25]. To solve the above problems, a vertical-frame-based setback arming device that also uses environmental force to release the safety is proposed in this paper, and low-speed wire electrical discharge machining (EDM) is successfully applied to the fabrication of the device.…”
Section: Introductionmentioning
confidence: 99%
“…For the fabrication of MEMS setback arming devices, nonsilicon-based micromachining technology (generally a lithography electroforming micro molding (LIGA) process or an ultraviolet-LIGA (UV-LIGA) process) and silicon-based micromachining technology (generally a deep reactive-ion etching (DRIE) process or a silicon-on-insulator (SOI) process) are commonly used. The cost of these processes is high, and no cheap mass production method has been found [24,25]. To solve the above problems, a vertical-frame-based setback arming device that also uses environmental force to release the safety is proposed in this paper, and low-speed wire electrical discharge machining (EDM) is successfully applied to the fabrication of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Three main methods are used to fabricate MEMS Safety and Arming devices. The first way is the ‘lithographie, galvanoformung, abformung’ (LIGA) method, which is based on metal substrates [ 12 , 13 , 14 , 15 ]. In this method, a MEMS metal spring and slide are needed, and the structures are set perpendicular to each other to form an interlocking mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the ball-driven MEMS setback arming device had appropriate safety and arming performance. There has been little research on the fabrication process of MEMS S&A devices; most researchers use the DRIE (deep reactive ion etching) process, LIGA process or UV-LIGA process to fabricate these devices [19]- [22]. These methods have many limitation, such as process complexity, high processing costs, large fabrication errors and long processing times [23]- [28].…”
Section: Introductionmentioning
confidence: 99%